Diagnosa Kerusakan Mesin Mobil Pada Bengkel Mobil Menggunakan Metode Certainty Factor - Fauzan, M. Arif (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Manual diagnosis of car engine damage in workshops often encounters obstacles, such as limited mechanic experience, lack of supporting tools, and low accuracy in identifying the root cause of the damage. This research aims to develop an expert system based on the Certainty Factor method to diagnose car engine problems. The method is used to measure the confidence level of symptoms based on input from mechanics and commonly found damage data. The study was conducted through in-depth interviews with workshop personnel to identify symptoms, types of damage, and commonly used diagnostic methods. The results show that the Certainty Factor approach can help provide more accurate and efficient diagnostic recommendations. This system is expected to improve the speed and reliability of the vehicle repair process.